Peran Pendidikan Islam Dalam Membentuk Karakter Bangsa Pasca Kemerdekaan - Patriana, Patriana; Yusdiansyah, Yusdiansyah; Hasyim Haddade; Arnadi, Arnadi (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
This research aims to analyze the reality of Islamic education in post-independence Indonesia which plays a role in building the character of the Indonesian nation, focusing on developments, challenges and future prospects. The research method carried out is through a Systematic Literature Review (SLR) regarding the literature sources used. from an indexing machine with a publication period between 2014 and 2024. Based on the results of literature analysis, post-independence Islamic education contributed to the development of national character. Islamic education currently has challenges that need to be considered, namely problems of resources, infrastructure and teacher quality which are serious obstacles to the effectiveness of Islamic education. Apart from that, issues related to the curriculum being less relevant to community needs and community recognition of Islamic education are also challenges that need to be overcome. Despite having challenges, Islamic education has good prospects. By improving the quality and relevance of education through technological integration, policy changes, and international cooperation, Islamic education will become global in the future.